Myocardial fibrosis evaluated by diffusion‐weighted imaging and its relationship to 3D contractile function in patients with hypertrophic cardiomyopathy. Issue 4 (30th March 2018) - Wu, Rui; An, Dong‐Aolei; Shi, Ruo‐Yang; Chen, Bing‐hua; Jiang, Meng; Bacyinski, Andrew; Han, Tong‐Tong; Hu, Jiani; Xu, Jian‐Rong; Wu, Lian‐Ming
Abstract : Background: Previous studies have shown that diffusion‐weighted imaging (DWI) is sensitive to myocardial fibrosis in ischemic and nonischemic cardiomyopathy. Purpose: To explore the prognostic value of apparent diffusion coefficient (ADC) for detecting myocardial fibrosis and its relationship to the contractile function in hypertrophic cardiomyopathy (HCM). Study Type: Prospective. Population: A total of 45 HCM patients and 20 controls. Field Strength/Sequence: 3.0T cardiac MRI. The cardiac MR sequences included cine, T1 mapping, and DWI. Assessment: According to the presence of late gadolinium enhancement (LGE) and the extracellular volume (ECV) values (+2 SD of control subjects), respectively, reader W and reader J assessed the value of ADC of each segment for detecting myocardial fibrosis and its relationship to impaired contractile function in HCM patients. Statistical Tests: Independent sample t ‐test, Pearson analysis, and intraclass correlation (ICC). Results: The value of ECV was 23.6 ± 3.0% for control. ECV ≥ 29.6% and ECV < 29.6% groups were classified. ADC values in the ECV ≥ 29.6% group were significantly increased compared to the ECV < 29.6% group, (2.41 ± 0.23 μm 2 /ms vs. 2.03 ± 0.16 μm 2 /ms, P  < 0.005). Compared to the LGE – group, ECV (32.1 ± 2.3% vs. 29.0 ± 2.8%, P  < 0.005) and ADC (2.60 ± 0.18 μm 2 /ms vs. 2.10 ± 0.07 μm 2 /ms, P  < 0.005) values were significantly increased in the LGE + group. ADC values were linearly associated with ECV values (R 2  = 0.65) in HCM patients. ADC values were linearly associated with circumferential and longitudinal strain (R 2  = 0.60, R 2  = 0.46), as well as circumferential, longitudinal, and radial strain rate (R 2  = 0.13, R 2  = 0.25, R 2  = 0.17, respectively). Data Conclusion: Contractile dysfunction in HCM is predominantly associated with ADC, which is a feasible alternative to ECV and LGE for detecting myocardial fibrosis. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1139–1146.